Bioaccumulation of Heavy Metals by Green mussel Perna viridis (Linnaeus ,1758) from Pekan, Pahang, Malaysia - John, Akbar; Yunus, Kamaruzzaman; Md Suhaimi, Mohd Zahir; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin (2010)
Numerous factors influences the bioaccumulation of heavy metal in mollusks tissues. Some time this accumulation may reach above the background concentration. Different tissues of any organism accumulate metals at different concentration and at different rates and the biological half-lives of metals at each type of soft tissues also differ from one another.Intertidal molluscs can be good biomonitoring organisms (Ismail, 2006)